“MODERN AND IN-DEPTH TEACHING METHODOLOGIES OF THE ENGLISH LANGUAGE FOR SCHOOL STUDENTS AND THEIR RELEVANCE IN TODAY’S WORLD” (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This article examines the methodological foundations of teaching English to school students in a deep and modern manner, the effectiveness of interactive approaches, the impact of digital learning tools on the educational process, and the relevance of English today as a global means of communication. In addition, it provides an in-depth analysis of the advantages of various methods such as communicative and integrative approaches, CLIL (Content and Language Integrated Learning), project-based learning, differentiated instruction, gamification, and STEAM in developing students’ language competencies. The article concludes with recommendations aimed at improving the quality of English language teaching in the school education system.